(untitled) (CIPEEX, 2025)
INTRODUCTION: Stereotactic radiosurgery (SRS) is a non-invasive technique that uses externally generated ionizing radiation to inactivate specific targets in the brain or column. It is indicated for patients with high surgical risk, such as elderly or multiple comorbidities, in addition to allowing access to deep or critical regions. Their main applications include treatment of cerebral and spinal metastases, neuralgia of the trigemeths, meningiomas, schwannomas and arteriovenous malformations (MAVs). OBJECTIVE: Analyze the relevance of SRS as a neurosurgical treatment for VAMs in patients with hemorrhagic stroke (HVAc). METHODOLOGY: A review was integrative literature in the databases PubMed, SciELO and LILACS, with search for articles published in the last 10 years. Original peer-reviewed studies were included, published in Portuguese, English or Spanish, with access to the full text and addressing the association between stereotactic radiosurgery, VAMs and HFCAs. Case reports were excluded, letters to the editor and studies that did not directly address the theme. RESULTS: The MAVs are complex vascular lesions in which arterial blood flows directly to the venous system by multiple fistulous communications and without capillary bed, generating hyperflow and increased risk of rupture. This condition is associated with the occurrence of HCVAh, especially in young adults, accounting for approximately 25% of cases in individuals with less than 50 years. SRS acts with converging radiation beams, causing vascular damage focal and promoting obliteration of AVM by endothelial proliferation. Additionally, it reduces pro-angiogenic mediators such as VEGF, TGFβ, angiopoietin-2 and growth factor basic of fibroblasts in up to three months, decreasing the risk of further bleeding. basic of fibroblasts in up to three months, decreasing the risk of further bleeding. CONCLUSION: Stereotactic radiosurgery is an effective, safe and minimally invasive and with lower cost, presenting low rate of complications. Your indication is relevant in more complex lesions or in patients with contraindications to conventional surgical treatment.